Tržaško vprašanje in Tržaška filharmonija - Sukljan, Nejc (Muzikološki zbornik, 2018)
This paper discusses the activities of the Trieste Philharmonic Orchestra (1945-1946) in the context of the concurrent political efforts to solve the Trieste question. An attempt to clarify the circumstances under which the orchestra was founded is then followed by a sketch of its organizational structure and a presentation of the orchestra's tour of the main Yugoslav centres and its political connotations. Finally, the circumstances under which the orchestra was dissolved are explained
Keywords: 1945-1946; filharmonije; glasba in politika; glasba in propaganda; muzikologija; sociologija glasbe; Trst; Tržaška filharmonija; tržaško vprašanje